Specifics of Distance Learning in the Modern Ukrainian Educational Space: Practices of the Higher Education Institutions of Ukraine - Iryna S. Sahaidak; Tetiana M. Chorna; Olena O. Balahura; Valentyna P. Bykhovchenko (Mukachevo State University, 2021)
Quarantine restrictions have increased the relevance of distance learning, and the level of information and communication technology development has made it possible for the Higher Education Institutions (HEIs) to switch to online mode, this being the optimal solution amid the pandemic. The object of this paper is to analyse the practical aspects of distance learning under quarantine and to identify the key factors affecting its efficiency. The assessment of the distant technologies use during the educational process and its efficiency was carried out by means of anonymous online questionnaire survey of the students from 4 higher education institutions: University of the State Fiscal Service of Ukraine, National Transport University, National University of Life and Environmental Sciences of Ukraine and Separated structural subdivision of the Kyiv College of Municipal Economy of The V.I. Vernadsky Taurida National University. The research has revealed the level of technical provision for distance learning; the level and practical experience of using distance technologies by the participants of the educational process was determined; the behavioural factors (students' attendance and teachers' adherence to the class schedule and thematic outlines) were examined; motivational factors of students' learning online were analysed; the most significant benefits of distance learning were examined; the higher education students' attitude to the blended and distance forms of learning was determined. It has been substantiated that distance learning organisation in the institution based on a single shared platform is a prerequisite for ensuring a highly effective online learning process. The practical value of the paper lies in the application of the survey results to enhance and increase the distance learning efficiency at the higher education institution level